(untitled) (Scientific journal of the Fergana State University, 2025)
This article extensively discusses the need to develop the musical thinking of young people in the new stage of societal progress. It emphasizes the importance of deeply embedding Uzbek music art into the consciousness of the youth, highlighting the beauty of maqom art, its miraculous nature, and the need to protect this ancient heritage as a precious treasure. The noble efforts aimed at preserving and imparting this heritage to the youth are reflected in the immense attention and care shown towards the development of national maqom art, which is vividly expressed in this article.